Physicochemical Properties and Antimicrobial Activity of Red Meranti (Shorea leprosula) Wood Powder Extract - Reski Agatri, Sagita; Raharjo, Dwi; Hartanti, Lucky (Department of Food Science and Biotechnology, Faculty of Agroindustrial and Biosystem Technology, Universitas Brawijaya, 2026)
Red meranti (Shorea leprosula) wood powder has potential as a natural preservative for coconut sap. This study investigated the effects of extraction temperature and time on the physicochemical properties and antimicrobial activity of red meranti wood powder extract. A randomized block design with two factors was used: extraction temperature (40, 50, 60, and 70 °C) and extraction time (30 and 60 min). Total phenolic, flavonoid, and alkaloid contents and antimicrobial activity against Saccharomyces cerevisiae were evaluated. The interaction between extraction temperature and time significantly affected all measured parameters. The optimum treatment was extraction at 70 °C for 30 min, yielding an inhibition zone of 37.32 mm, a total flavonoid content of 42.11 mg QE/g extract, a total phenolic content of 304.13 mg GAE/g extract, and a total alkaloid content of 2.76%.